INCREASING THE EFFECTIVENESS OF YOUTH ENTREPRENEURSHIP TRAINING PROCESSES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Youth entrepreneurship training is a powerful tool for addressing unemployment and fostering economic growth. However, many programs struggle to achieve desired outcomes due to their theoretical nature, lack of practical application, and insufficient post-training support. This thesis examines strategies to enhance the effectiveness of these programs by emphasizing experiential learning, integrating mentorship, and leveraging digital tools. Addressing systemic barriers such as limited access to funding, markets, and infrastructure is also critical. Furthermore, fostering an entrepreneurial mindset, characterized by creativity, resilience, and adaptability, equips young entrepreneurs to navigate challenges and seize opportunities.